Mode-mixing-induced second harmonic A0 mode Lamb wave for local incipient damage inspection. (1st April 2020) - Shan, Shengbo; Cheng, Li
Abstract: This paper reports the discovery of a special type of second harmonic A0 mode Lamb wave, which is generated through the mixing of primary S0 and A0 mode Lamb waves in a PZT-activated weakly nonlinear plate. Owing to the different propagating velocities of the S0 and A0 waves and the finite duration of their corresponding tone-burst wave packets, wave mixing takes place within a confined area which can be precisely controlled by tuning the wave excitation durations. When local incipient damage falls into the mixing zone, this second harmonic A0 mode wave provides higher damage detectability than the commonly used second harmonic S0 mode wave resulting from the global material nonlinearity. Moreover, through a tactic tuning of the mixing zone size, damage detection can be carried out zone by zone along the transmitter–receiver path to achieve damage localization. Finite element (FE) simulations are first carried out to ascertain the theoretically predicted phenomenon and the underlying generation mechanism of the second harmonic A0 mode Lamb waves. Capitalizing on its mode mixing feature between the primary A0 and S0 mode Lamb waves, a dedicated damage localization strategy alongside the corresponding algorithm is then proposed. Experiments are finally carried out with a dedicatedly designed inspection system with mitigated non-damage-related nonlinear interference. Both FE and experimental results demonstrate the appealing characteristics and the potential of the second harmonic A0 mode Lamb waves for local incipient damage detection and localization.